2020
DOI: 10.2196/14565
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategies for Virtual Reality Interventions for Managing Pain and Anxiety in Children and Adolescents: Scoping Review

Abstract: Background Virtual reality (VR) technology has been explored in the health sector as a novel tool for supporting treatment side effects, including managing pain and anxiety. VR has recently become more available with the launch of low-cost devices and apps. Objective This study aimed to provide an updated review of the research into VR use for pain and anxiety in pediatric patients undergoing medical procedures. Methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 39 publications
2
76
0
Order By: Relevance
“…Our findings suggest distraction paired with stimulating emotional experiences such as positive surprise, is desirable and may help children disconnect from distressing elements of the environment. Positive emotions are shown to alleviate psychological stress [ 22 ] and improve the efficacy of distraction through VR [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our findings suggest distraction paired with stimulating emotional experiences such as positive surprise, is desirable and may help children disconnect from distressing elements of the environment. Positive emotions are shown to alleviate psychological stress [ 22 ] and improve the efficacy of distraction through VR [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of the 10 design factors generated based on our findings reveals the complexities and potential challenges in meeting the experiential, psychological, and intervention needs of pediatric patients and their carers through one VR solution. Ahmadpour et al [ 18 ] called for skill-building in VR to allow patients to become active agents in their care in a variety of ways. Building meaningful skills in VR necessitates a holistic approach due to the temporality of periprocedural experience with different needs becoming prominent at different stages of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the ways of addressing these challenges include simulation-based learning using the latest technologies (eg, virtual reality [VR], which has generated a growing interest in recent years [ 15 ]). Studies have demonstrated improved performance when using VR for basic life support training [ 16 ], but there is limited information about what users of ALS systems need, specific design considerations, and ways we can improve user experience and engagement with the training [ 17 ].…”
Section: Introductionmentioning
confidence: 99%